2020
DOI: 10.1364/oe.387794
|View full text |Cite
|
Sign up to set email alerts
|

Doublet metalens design for high numerical aperture and simultaneous correction of chromatic and monochromatic aberrations

Abstract: Metalens is one of the most prominent applications among metasurfaces since it gives possibilities to replace the conventional lenses for compactness and multi-functionalities. Recently, many studies have been demonstrated to overcome the aberrations of the metalenses for high performance practical applications. Previous studies have used the methods that control the dispersion of meta-atoms for correcting chromatic aberrations and use doublet platform for correcting monochromatic aberrations. Despite these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Finally, in terms of applicability, we expect that this scheme can be more useful in designing novel optical setups and can be compatible in various conventional setups, which would lighten the weight of optical devices. [41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in terms of applicability, we expect that this scheme can be more useful in designing novel optical setups and can be compatible in various conventional setups, which would lighten the weight of optical devices. [41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…Inspired from the above early studies on chromatic and monochromatic aberration compensations, C. Kim et al ( Figure 5 d) reported doublet metalens optimization research [ 26 ]. In the study, the authors found that simultaneous correction of LCA, transverse chromatic aberration (TCA), and the five monochromatic aberrations is almost impossible in the doublet p-Si metalens.…”
Section: Focusing and Imaging Performance Of Dielectric Metalensesmentioning
confidence: 99%
“…( ii ) Captured sample images and corresponding ( iii ) modulation transfer functions for sagittal (dashed lines) and tangential (solid lines) ray directions. ( d ) Doublet silicon metalens optimization for simultaneous correction of chromatic and monochromatic aberrations at the three colors [ 26 ]. ( i ) Concept diagram, ( ii ) color filtering efficiency of the backside metalens, and ( iii ) optimized performance comparison.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional refractive or diffractive lenses (Lalanne et al, 1999;Khorasaninejad et al, 2015;Lin et al, 2014), the physical working principles of metalenses are more diverse, so they present additional ways to rectify unwanted aberration. Metalenses even offer a way to solve both monochromatic and achromatic focusing problems simultaneously (Kim et al, 2020c;Arbabi et al, 2016a).…”
Section: Aberration Correctionmentioning
confidence: 99%